The predictive ability of the talent development environment on youth elite football players' well-being: A person-centered approach - Ivarsson, A.; Stenling, A.; Fallby, J.; Johnson, U.; Borg, E.; Johansson, G. (Psychology of Sport and Exercise, 2015)
Objective:The objective of this study was to examine the predictive ability of perceived talent development environment (TDE) on the well-being of youth elite football players. Design: A field-based longitudinal design was employed. Method: The participants were 195 Swedish youth elite football players between 13 and 16 years of age enrolled at Swedish football academies. The players responded to questionnaires regarding their perceptions of their TDE, perceived stress, and well-being in the beginning of the competitive season 2012 (T1). On two more occasions, six and 12 months later, the players completed the stress and well-being questionnaires. Results: A latent class analysis, based on the TDEQ sub-scale scores at T1, revealed three classes of players with different perceptions of their TDE (one high quality, one moderate quality, and one poor quality class). A second-order multivariate latent growth curve model (factor-of-curves model) showed that the class of players perceiving the lowest TDE quality, experienced higher initial level of stress and lower initial level of well-being at T1 compared to the other two classes. Moreover, there were no significant differences in slopes for neither stress nor well-being between classes (the initial difference between the three groups, in well-being, remained stable over time). Conclusion: The results indicate that players perceiving their TDE as supporting and focusing on long-term development seem to be less stressed and experience higher well-being than other players. Hence, in addition to facilitate sport-specific development and performance among youth athletes, high quality TDEs may be important for youth elite athletes' general well-being.